1996
DOI: 10.1136/bmj.313.7069.1355
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diagnosis of ovarian cancer after raised serum CA 125 concentration: a prospective cohort study

Abstract: Objective-To determine the risk of invasive epithelial ovarian cancer and fallopian tube cancer associated with a raised concentration of the tumour marker CA 125 in asymptomatic postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(95 citation statements)
references
References 15 publications
1
88
0
6
Order By: Relevance
“…The specificity of screening with CA125 was initially improved by the use of pelvic ultrasound as a second-line test to assess ovarian volume and morphology. Using multimodal screening incorporating sequential CA125 and pelvic ultrasound, a specificity of 99.9% and PPV of 26.8% (ϳ4 operations for each cancer) for detection of ovarian and fallopian tube cancer was achieved in 22,000 postmenopausal women (63,64). With the accumulation of data in this study, ovarian morphology has been used to refine algorithms for the interpretation of ultrasound in postmenopusal women with elevated CA125 levels (65,66).…”
Section: Ovx1mentioning
confidence: 99%
“…The specificity of screening with CA125 was initially improved by the use of pelvic ultrasound as a second-line test to assess ovarian volume and morphology. Using multimodal screening incorporating sequential CA125 and pelvic ultrasound, a specificity of 99.9% and PPV of 26.8% (ϳ4 operations for each cancer) for detection of ovarian and fallopian tube cancer was achieved in 22,000 postmenopausal women (63,64). With the accumulation of data in this study, ovarian morphology has been used to refine algorithms for the interpretation of ultrasound in postmenopusal women with elevated CA125 levels (65,66).…”
Section: Ovx1mentioning
confidence: 99%
“…Although the role of CA125 in screening remains controversial, there is evidence that serum elevation is associated with an increased risk of ovarian cancer. We have previously reported that asymptomatic postmenopausal women with a CA125 ≥ 30 U ml -1 have a 36-fold increased risk of diagnosis for ovarian cancer in the subsequent year (Jacobs et al, 1996). This data was derived from a multimodal screening study which used pelvic ultrasound as a secondary test.…”
mentioning
confidence: 99%
“…The value of tumour antigen CA 125 for the early diagnosis of ovarian cancer in premenopausal women is limited because non-malignant conditions such as endometriosis or infections are also associated with increasing serum levels of CA 125 (Jacobs and Bast, 1989;Oram and Jeyarajah, 1994). However, even in post-menopausal women, the value of serum CA 125 level for early diagnosis of ovarian cancer is under investigation because it is elevated in a significant number of patients with early-stage disease (Jacobs et al, 1996).…”
mentioning
confidence: 99%